Managing 3D spatial objects using geo DBMS and microstation geographics - Mohamad Zulkifli, Siti Nur Awanis (Penerbit UTM, 2008)
Nowadays, GIS users are getting more complex datasets and needs to manipulate and generate information, as we perceived in the real world, i.e. in 3D environment. This environment provides better understanding of geospatial pattern and phenomena either in small or large areas (Zlatanova et. al 2002). Relevant questions such as: How we model the real world object, i.e. 2D and 3D spatial objects in DBMS and visualizing the objects in GIS/CAD front-end? Answering this question provides an interesting experiment toward realizing 3D geospatial database. In general, many organisations realize the needs for a central DBMS: a system contains spatial and attribute data maintained in one integrated environment. Many DBMSs are capable of maintaining spatial data in 2D, since spatial data types and data structure in 2D implemented in DBMSs. However, aspect of 3D data still needs many efforts to address.